Indonesian and Singapore Manufacturing Companies: Analysis of Differences in Company Profitability during the Pandemic - Asmarawati, Sandra Galuh; Dewi, Adhita Maharani (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Profitability is the ability of a company to earn profits during a period. In 2019, the world was hit by the Covid-19 pandemic which caused disruption to the world economy. Researchers want to look for evidence regarding the company's financial, especially the company's profitability during Covid-19 in Indonesia and Singapore. This research aims to analyze and obtain empirical evidence regarding the differences in the profitability of Indonesia’s manufacturing companies and Singapore. The research method uses the Independent Sample t Test of mean difference with samples from manufacturing companies listed on the Indonesia Stock Exchange (IDX) and Singapore manufacturing companies listed on the Singapore Exchange (SGX) during 2018–2022. Profitability variables use the Return on Assets (ROA) and Net Profit Margin (NPM) ratios. The research results show that there are differences in the average NPM and ROA between Indonesian and Singaporean manufacturing companies.